Validity and reliability of eating disorder assessments used with athletes: A review - Pope, Z.; Gao, Y.; Bolter, N.; Pritchard, M. (Journal of Sport and Health Science, 2015)
Background: Prevalence of eating disorders (EDs) among college-aged athletes has risen in recent years. Although measures exist for assessing EDs, these measures have not been thoroughly reviewed in athletes. This study reviewed the validity and reliability evidence of the commonly used measures for assessing EDs in athlete populations aged 18-26 years. Methods: Databases were searched for studies of regarding ED on male and/or female athletes. Inclusion criteria stated the study (a) assessed EDs in an athlete population 18-26 years of age and (b) investigated EDs using a psychometric measure found valid and/or reliable in a non-athlete population and/or athlete population. Results: Fifty studies met the inclusion criteria. Seven and 22 articles, respectively, studied EDs behaviors in male and female athletes whereas 21 articles studied EDs in combined-gender samples. The five most commonly used measures were the Eating Attitudes Test (EAT), Eating Disorder Inventory (EDI), Bulimia Test-Revised (BULIT-R), Questionnaire for Eating Disorder Diagnosis (QEDD), and the Eating Disorder Examination Questionnaire (EDE-Q). Conclusion: Only seven studies calculated validity coefficients within the study whereas 47 cited the validity coefficient. Twenty-six calculated a reliability coefficient whereas 47 cited the reliability of the ED measures. Four studies found validity evidence for the EAT, EDI, BULIT-R, QEDD, and EDE-Q in an athlete population. Few studies reviewed calculated validity and reliability coefficients of ED measures. Cross-validation of these measures in athlete populations is clearly needed.